2017
DOI: 10.1002/jgm.2973
|View full text |Cite
|
Sign up to set email alerts
|

Association of incretin receptors genetic polymorphisms with type 2 diabetes mellitus in Egyptian patients

Abstract: We reveal for the first time an association between the GIPR rs2302382 polymorphism and T2DM in Egyptians. Yet, there was no significant association of GIPR rs1800437 or GLP-1R rs367543060 with T2DM risk. The haplotype A (rs2302382) C (rs1800437) was associated with an increased risk of T2DM. Furthermore, there was a significant increase of GIP and a significant decrease of GLP-1 levels when diabetic patients were compared with controls. An important finding was that there was a relationship between both GIPR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Associations with T2DM risk were investigated in a study that included 150 T2DM patients and 150 healthy controls from Egypt. This study found no association of GLP1R rs367543060 polymorphism with T2DM, although they have observed significantly lower GLP-1 levels in diabetic patients than controls [ 62 ].…”
Section: Genetic Variability Of the Incretin Systemmentioning
confidence: 85%
“…Associations with T2DM risk were investigated in a study that included 150 T2DM patients and 150 healthy controls from Egypt. This study found no association of GLP1R rs367543060 polymorphism with T2DM, although they have observed significantly lower GLP-1 levels in diabetic patients than controls [ 62 ].…”
Section: Genetic Variability Of the Incretin Systemmentioning
confidence: 85%
“…Shalaby group [24] studied rs1800437 polymorphism in Egyptian T2DM patients. Their findings indicated that the distribution of C haplotype is statistically higher in patients than controls.…”
Section: Discussionmentioning
confidence: 99%
“…This variant was also independently associated with protection against coronary heart disease [61]. Additionally, GLP-1R genetic polymorphisms have been associated with increased T2DM and/or coronary heart disease risk in East Asian [66], Egyptian [67], Japanese [63,68] and Chinese populations [69].…”
Section: Polymorphisms Of the Glp1r Genementioning
confidence: 96%